SISTEM PENDUKUNG KEPUTUSAN FAKTOR-FAKTOR PENYEBAB KETERLAMBATAN AUDIT PADA PERUSAHAAN MENERAPKAN METODE AHP (STUDI KASUS: KANTOR AKUNTAN PUBLIK) - Mawaddah, Isnaini (TIN: Terapan Informatika Nusantara, 2020)
The accuracy of the company in publishing financial statements may experience delays caused by the duration of auiditor in completing its audit work. The auditor conducts his audit duties based on the professional public accountant (SPAP) standard. With sampling techniques use purposeve sampling. Namely the selection of certain considerations where the safeguards are generally adapted to testing or research problems. This research method applies the AHP (Analaitycal Hierarchy Process) method. Every financial report provided by the company is a very important source of information within the agency, if there is a delay in the delivery, the information presented is less accurate. , internal audit, company size and timeliness. The results of this study indicate that profitability has a very significant effect on audit reliability, whereas, solvency, internal audit, while solvency, internal audit, company size and timeliness do not significantly influence audit delay. This research is expected to have sufficient implications means for the parties involved in assessing and predicting the timely submission of financial statements